Convergence at the Crime Scene: Multidisciplinary Science in Contemporary Criminal Justice - Rakesh Nair (AG Volumes, 2026)
The convergence of multiple scientific disciplines has transformed contemporary criminal justice by enhancing the accuracy, reliability, and efficiency of criminal investigations. It is an overview of the multidisciplinary science in contemporary forensic science, focusing on the integration of the concepts of crime scene investigation, digital forensic, forensic psychology, evidence management, artificial intelligence, and data analytics. The study underscores the importance of collaboration among forensic scientists, psychologists, digital investigators, engineers, and legal professionals in the collection, interpretation, and decision-making process in court cases. Cybercrime investigations have been enhanced by developments in digital forensic technologies and behavioral profiling has enhanced the knowledge of offender characteristics and investigative strategies. In addition, AI and data analytics have revolutionized forensic investigations by streamlining evidence handling, pattern recognition, and predictive analysis. Despite these developments, issues of evidence integrity, algorithmic bias, privacy, ethics, and the admissibility of evidence remain to have an impact on forensic practice. In conclusion, the integration of multiple scientific disciplines into the field of criminal justice has emerged as a cornerstone of modern operations, enhancing the effectiveness of investigations, aiding evidence-based decision-making, and ensuring justice and accurate judgments in the courtroom.